2017
DOI: 10.3390/brainsci7070079
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Mild Traumatic Brain Injuries Are Associated with Increased Rates of Health Symptoms and Gulf War Illness in a Cohort of 1990–1991 Gulf War Veterans

Abstract: Recent research demonstrated a relation between traumatic brain injury (TBI), health symptoms and diagnosis of Gulf War Illness (GWI) in Gulf War Veterans, but no study has examined the impact of multiple mild TBIs (mTBIs). A total of 229 male Gulf War Veterans from the Ft Devens Cohort were categorized by a number of mTBIs reported. One-way ANOVA and chi-square test of independence were used to test for differences in total reported health symptoms and diagnosis of chronic multisymptom illness (CMI) or Kansas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 36 publications
4
26
0
Order By: Relevance
“…Given the brevity of the GW ground war, mTBI has not been investigated as a primary factor of GWI until recently. In our recent work with the Ft. Devens Cohort, veterans with mTBI had increased rates of GWI as determined by Centers for Disease Control (CDC) and Kansas GWI criteria [ 16 , 17 ]. These studies also showed that the increased number of mTBIs was associated with higher number of total symptoms reported [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the brevity of the GW ground war, mTBI has not been investigated as a primary factor of GWI until recently. In our recent work with the Ft. Devens Cohort, veterans with mTBI had increased rates of GWI as determined by Centers for Disease Control (CDC) and Kansas GWI criteria [ 16 , 17 ]. These studies also showed that the increased number of mTBIs was associated with higher number of total symptoms reported [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our recent work with the Ft. Devens Cohort, veterans with mTBI had increased rates of GWI as determined by Centers for Disease Control (CDC) and Kansas GWI criteria [ 16 , 17 ]. These studies also showed that the increased number of mTBIs was associated with higher number of total symptoms reported [ 16 ]. However, the timing of the mTBI was not available for the Ft. Devens Cohort studies, leaving open the question of whether the proximity of the mTBI to CBW exposure had an impact on the rates of GWI and comorbid chronic health conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The investigation of dizziness/vertigo symptoms and vestibular dysfunction in Gulf War veterans is complicated by the presence of mental health comorbidities and traumatic brain injury (TBI). Gulf War veterans, and deployed veterans in general, experience higher rates of anxiety, posttraumatic stress disorder (PTSD), depression, and TBI (Black et al, 2004;Bierer et al, 2015;McKenzie et al, 2015;Yee et al, 2017) when compared with civilian and nondeployed military populations.…”
mentioning
confidence: 99%
“…A recent series of studies has considered the impact of TBI on the presence of chronic multisymptom illness in Gulf War veterans, finding increased self-reported mild TBI is related to an increase in physical symptom burden (Yee et al, 2017). These authors suggested that the combined effects of head injury and exposures in Gulf War veterans may promote persistent neuroinflammation thought to be at the root of GWI symptoms (Yee et al, 2017). Mild TBI has also been shown to have a persistent negative influence on vertigo/dizziness symptoms in approximately one-third of individuals (Fife and Kalra, 2015).…”
mentioning
confidence: 99%